2022
DOI: 10.1002/adom.202201423
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent Conjugated Polymer as the Counter Electrode in Electrochromic Smart Windows

Abstract: mirrors, [2] electronic paper, [3] spacecraft thermal control, [4] and military camouflage, [5] etc.Generally, there are five functional layers in one electrochromic device (ECD): two conductive layers, one electrochromic layer, one electrolyte layer, and one counter electrode layer (i.e., the ion storage layer). Among those, the electrochromic layer is responsible for the color transformation. The counter electrode layer coordinates the redox reaction of the electrochromic layer, storing the counter ions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The ion storage layer functions as a counter electrode layer, undergoing reversible electrochemical oxidation (reduction) to coordinate the reduction (oxidation) of the EC material to balance the charge shuttling from the EC layer through the electrolyte. [45][46][47] The electrolyte layer sits in the center of the device, which can separate the EC layer and ion storage layer to prevent direct electrical contact and transport ions inside the device. 48 Substrates and conducting layers as conductive electrodes which determine the mechanical properties of the devices are commonly discussed together.…”
Section: Structure Of Ec Devices For Camouflagementioning
confidence: 99%
See 2 more Smart Citations
“…The ion storage layer functions as a counter electrode layer, undergoing reversible electrochemical oxidation (reduction) to coordinate the reduction (oxidation) of the EC material to balance the charge shuttling from the EC layer through the electrolyte. [45][46][47] The electrolyte layer sits in the center of the device, which can separate the EC layer and ion storage layer to prevent direct electrical contact and transport ions inside the device. 48 Substrates and conducting layers as conductive electrodes which determine the mechanical properties of the devices are commonly discussed together.…”
Section: Structure Of Ec Devices For Camouflagementioning
confidence: 99%
“…The result demonstrated that the device retained the color switching of EC materials while also showing high longterm durability (95% retention of the contrast after 3300 steps), fast response time (less than 4 s) and excellent coloration efficiency. In addition, other colorless ionic storage layers, such as inorganic oxides, 129,130 poly(2,2,6,6-tetramethylpiperidinyloxy-4-ylmethacrylate) (PTMA) derivatives, [131][132][133] and conjugated polymers, 43,46 could also be applied to camouflage devices. Notably, the matched electroactive voltage window of the ion storage material and the EC material is also a major influence on device performance.…”
Section: Ec Devices For Color Camouflagementioning
confidence: 99%
See 1 more Smart Citation
“…Conjugated polymers are an attractive class of electrochromic materials owing to their easily modified structure, tunable bandgaps, and facile optical properties. [1][2][3] Solution-processable conjugated polymers are likely to play an important role in DOI: 10.1002/smll.202303359 low-cost and large-scale production of electrochromic materials, which is of great value in their practical applications. [4,5] Conventionally, the introduction of solubilizing groups (such as long alkyl chain or alkoxy chain) is a necessary and common method to obtain solution-processable polymers.…”
Section: Introductionmentioning
confidence: 99%
“…As a new generation of electrochromic (EC) materials, conjugated polymers are widely used for their fast switching time, high contrast, and coloration efficiency, as well as easy structural modification, providing a broad platform for designing and preparing high-performance electrochromic materials. Solution-processable conjugated polymers have important applications in low-cost, large-scale production of electrochromic materials. Black-to-transparent solution-processable conjugated polymers are a special and rare class of materials used in reflective and transmissive electrochromic devices, including user-controlled protective eyewear, dimmable windows, and electronic paper, which have received much attention in the field of electrochromic materials. …”
Section: Introductionmentioning
confidence: 99%